Lung squamous cell carcinoma with severe hypomagnesemia due to cisplatin plus gemcitabine in combination with necitumumab therapy: A case report. Issue 13 (1st June 2021) - Nakao, Akira; Inoue, Hiroyuki; Osaki, Yusuke; Hirano, Ryosuke; Harada, Taishi; Aoyama, Takashi; Igata, Fumiyasu; Fujita, Masaki
Abstract: A 72‐year‐old man, diagnosed with advanced lung squamous cell carcinoma, was administered of cisplatin plus gemcitabine with necitumumab, a human monoclonal antibody that binds to the epidermal growth factor receptor (EGFR), as a sixth‐line treatment. Tumor shrinkage was observed, but asymptomatic grade 4 hypomagnesemia occurred on day 8 of the second cycle. He received magnesium replenishment and hypomagnesemia recovered on day 40, but tumor progression was observed during the period of magnesium correction. Hypomagnesemia is known as a major adverse event of treatment with anti‐EGFR antibodies, but there have been no case reports of severe hypomagnesemia or its clinical course. Abstract : An unusual case in which we successfully corrected the grade 4 hypomagnesemia as a severe adverse event via intravenous supplementation in the treatment for squamous non‐small cell lung cancer. ​